Validity and reliability of a novel Color-Risk Psychiatric Triage in a psychiatric emergency department - Molina-López, Alejandro (BMC Psychiatry, 2016)
BACKGROUND: Classification of Psychiatric Emergency Presentations (PEP) is not sufficiently clear due to their inherent high inter-subjectivity and lack of validated triage instruments. In order to improve current classification of psychiatric emergency presentations (PEP) at Emergency Departments, we implemented and validated the Color-Risk Psychiatric Triage (CRPT), an instrument for classifying PEP risk by sorting one to five color/risk levels and one to thirty-two possible conditions arranged by risk. METHODS: Users who visited the Emergency Department (ED) of a Mexican psychiatric hospital from Dec 1st, 2008 to Dec 1st, 2009 were included. One CRPT was assessed by an ED psychiatrist to each patient upon their arrival to ED. Some patients were randomly assessed simultaneously with an additional CRPT and a Crisis and Triage Rating Scale (CTRS) to test validity and reliability of the CRPT. RESULTS: A total of 7,631 CRPT assessments were included. The majority of PEP were non-urgent (74.28 %). For the validation phase n = 158 patients were included. CRPT score showed higher concurrent validity than CRPT color/risk. CRPT level/risk and score showed highest concurrent validity within dangerousness domain of CTRS (r = 0.703, p < 0.0001). CRPT and CTRS scores showed similar predictive validity (p < 0.0001). High intraclass correlation coefficient (0.982) and Cohen’s Kappa (0.89) were observed for CRPT score (r = 0.982, p < 0.0001). CONCLUSIONS: CRPT appeared to be a useful instrument for PEP classification due to its concurrent validity, predictive validity and reliability. CRPT score showed higher correlations than the CRPT color/risk. The five levels of risk provided by the CRPT appear to represent a simple and specific method for classifying PEP. This approach considers actual or potential risk, rather than severity, as the main factor for sorting PEP, which improves upon the current approach to emergency classification that is mainly based on the criterion of severity. Regardless of the triage procedure, emergency assessments should no longer classify PEP as “not real emergencies.” ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-016-0727-7) contains supplementary material, which is available to authorized users.